A Descriptive Study On Etiological Factors of Kabala Kanaapu (Sinusitis) Among Patients in Kodikamam-J/327 Gs Division, Jaffna District - Miraaj, R.; Sailajah, S. (Global Academic Research Institute Colombo, Sri Lanka, 2022)
Kabalakkanapu (Sinusitis) is one of the common disorder seen by the general practitioners, which are troubling the mankind. Although Kabalakkanapu is create physical and psychological discomfort. Sinusitis can be broadly defined as inflammation of one or more of the para nasal sinuses. The paranasal sinuses are lined with mucous membranes that have tiny hairs on them (ciliated epithelium). These mucous membranes produce a secretion that runs down through the nose and throat. Sinusitis is an inflammation or swelling of the tissue lining the sinuses. Acute sinusitis symptoms are facial pain and pressure, blocked nose, nasal discharge, reduced sense of smell, congestion and post nasal drip. These symptoms are more similar to Kabalakkanapu which is mentioned in the Siddha text book of Parajasekaram-Siroroga nithanam. I made my research involving 50 members diagnosed as Kabalakkanapu patients. Questionnaire was text book. Made on the basis of Siddha concept of etiological factors of Kabalakkanapu said in Siddha text book. At the end of the study, I have really realized that “Prevention is better than cure” because the people who were exposed to the etiological factors of Kabalakkanapu without awareness were gotten the asthmatic episodes. If we make awareness about the etiological factors of Kabalakkanapu, the patient will take care of their own health. From this study results and observation, I found that the patient having H/O, exposure to dust and other allergens was 46 members (92%); H/O, exposures to cool air and intake of cold water was 38 members (76%); H/O, patients with nasal septal deviation was 14 members (28%) & nasal polyps was 12 members (24%); H/O, allergic to cosmetics was 20 members (40%). This study will be essential role of siddha physicians to early diagnosis, prognosis and prevention of the disease. Further literary and clinical studies are necessary in future.
Keywords: Kabalakkanapu; Sinusitis; Descriptive cross-sectional study